Theater, work and affections in the Podestá’s Argentinian companies-families during the end of the 19th century and the beginning of the 20th - Noguera, Lía Sabrina (2022)
The Podestás are the founding family in what refers to theatrical activity in Argentina. Its family tree houses more than a hundred members (mostly artists) and covers the time span from the end of the 19th century to the 20th century. In this article, we focus on the study of what we have called ‘companies-families’, a category that responds to and evidences the blood ties established between its members and the marriage contracts also produced with artists from the local artistic field. From a study that contemplates the aesthetic, labor conditions and the incidence of affective ties, for their formations and for their ruptures, we center on the analysis of the companies-families formed in Buenos Aires by Jerónimo Podestá and Pablo Podestá between 1880 and 1920.